The protective role of ureteral stents in reducing fibrosis and preventing stricture in ureteral injuries of different severities - Hao Gu; Tingting Yang; Zhimin Qin; Siyuan Zhang; Liangyong Wang; Zeju Zhao (BMC Urology)
Abstract Purpose Ureteral injuries following endoscopic interventions often lead to fibrosis and subsequent stricture formation, yet the optimal use and duration of ureteral stents in preventing these outcomes remain unclear. This study aimed to determine whether ureteral stents have an inhibitory effect on fibrosis development and provide evidence to optimize stent use and duration. Methods This study was conducted between March and October 2023. Rabbit models with varying degrees of ureteral injury (G1-G4) were established according to the Post-Ureteroscopy Lesion Scale (PULS), dividing into Control (no ureteral stent placement), 2-week (stent placed for 2 weeks), and 4-week (stent placed for 4 weeks) groups. Ureteral tissues from G1-G4 models were collected at 2- and 4-weeks post-operation for HE staining, Masson staining, RT-PCR, and Western Blot to measure the levels of TGF-β1, α-SMA, and Collagen I expressions. Results Stent placement in ureteral injury models significantly reduced inflammatory cell infiltration and collagen deposition, thereby mitigating fibrosis, with the most pronounced effects observed in more severe injuries (G3 and G4). At both 2- and 4-weeks post-operation, stented groups showed less inflammation and fibrosis compared to stentless groups, demonstrating the protective effect of stents. The expression of fibrosis-related proteins (TGF-β1, Collagen I, and α-SMA) in ureteral tissues increased with the severity of injury (G1-G4) at both 2- and 4-weeks post-operation. Conclusions Placement of a ureteral stent can inhibit fibrosis in G2-G4 level ureteral injuries, preventing ureteral stricture and occlusion. Ureteral stents are suggested to place for more than 4-weeks for injuries beyond the submucosal layer.